Communicative Dialogue in the Light of the Holy Qur’an and the Prophetic Sunnah: An Objective Study - كاظم, دعاء شكر عباس (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This research presents an objective study aimed at extracting the theoretical and practical foundations of civilizational dialogue in Islam, based on the Holy Quran and the Prophetic Sunnah. It emphasizes that Islam, with the comprehensiveness of its message, represents a rich and abundant referential framework for building bridges of communication between peoples. The sources of Islamic legislation are replete with valuable directives calling for constructive dialogue, respect for the other, cooperation for good, and the rejection of intolerance. The significance of this study lies in its endeavor to understand and activate the directives of Islamic law (Sharia) in civilizational relations, to contribute to building a more peaceful and just world, and to enrich the academic discussion on the concept of dialogue from an authentic Islamic perspective. The research has been divided into an introduction that addresses the concept of dialogue and its pillars, three chapters that examine the grounding of dialogue in the Quran and Sunnah, and a conclusion highlighting the most important findings. The research clarifies that dialogue in Islam is an original method of Da'wah (invitation to Islam), and it is based on the presence of two conversing parties who abandon prejudice, a specific issue for dialogue, and a peaceful approach that adopts goodness (Husna). It also distinguishes between dialogue and debate (Jadal), emphasizing the importance of good debate in Da'wah with the People of the Book and others. Furthermore, the research demonstrates the grounding of dialogue in the Quran through numerous verses and diverse methods of argumentation, and in the Prophetic Sunnah through the Prophet's stances and his dialogues with various parties. The research concludes that civilizational dialogue holds great importance in Islam, and that the Quran and Sunnah focused on serious and beneficial dialogue based on intellectual freedom and common human values, emphasizing the significance of wisdom and good counsel in Da'wah. It also highlights that dialogue and culture are crucial axes in the lives of peoples, necessitating the acceptance of the culture of the other and exchange with it.